Strange usurped potentates: Elizabeth I, the papacy and the Indian summer of the medieval deposing power - Lock, J (1992)
This thesis centres on a pivotal event in the development of religious antagonism in England - the papal excommunication and deposition of Elizabeth I - considering its origins and consequences, especially its effect on Protestant thought and writing (since the political thought of Elizabethan Catholics has undergone more recent study). The event appears as a revival of a claim not so antiquated as it is sometimes seen. I survey the medieval precedents for the papal claim to depose secular princes, which have lacked an overall survey, and the (often exaggerated) sixteenth-century views as to its past influence. There was indeed an exceptionally acute sense of this aspect of history during the early English Reformation. The effect of this was that the actual deposition in 1570 served only to confirm Protestants’ preconceptions. In their views of history, they tended towards a conspiracy theory whereby the influence of Pope and prelates lay behind most, if not all, opposition to English and European monarchies. In their views of contemporary foreign affairs, they had, since the beginning of Elizabeth's reign, constantly suspected the machinations of a (fictional) Catholic League, whereby Catholic powers, probably in conjunction with an internal rising, would combine to destroy Protestant England. This would be heralded by the constantly predicted papal sentence against Elizabeth. Demonstrably, this was not the case. Disagreements among Catholic potentates precluded any such agreement in the early part of Elizabeth's reign; and ensured that, when Pius V did issue his sentence, it proved a dangerous embarrassment (in no way mitigated by Gregory XIII's qualification of it). It did serve a pivotal role in actual Catholic plans, which however were unable to overcome conflicting interests; the result was notoriety without efficacy. Nevertheless, a paranoid and pessimistic view predominated in Protestant England, diminishing only Slowly even when overt confrontation late in the reign began to be crowned with success. Constant alertness for conflict had proved something of a self-fulfilling prophecy.